Home-advantage in table tennis league competitions - Paár, D.; Linder, A.; Laczko, T. (Proceedings Book of The 16th ITTF Sports Science Congress Budapest (HUN), April 19th - 20th, 2019, 2020)
Home-advantage researches examine the performance difference of teams and athletes between home field or halls and away field or halls. A non-typical aspect of researching the presence or absence of home-advantage in table tennis is the balanced (e.g. national leagues) schedules perspective. A previous paper didn`t find the home-advantage as a significant phenomenon in the men`s German Bundesleague 1. The Austrian Bundesleague 1`s team matches between 2008 and 2018 were examined. 46% of the matches ended with a home victory, 41% ended with a guest victory and 14% ended with a draw. The presence of home-advantage was significant for the final result of team matches (Z(604) = -2.910, p < 0.01) and for the difference of won and lost individual matches by the home teams (Z(604) = -3.623, p < 0.01). There was no significant difference between top, average and low level teams in the difference of home and away winning ratio (Chi²(114) = 1.339, p > 0.5) and in the difference of gathered individual matches at home and away (Chi²(114) = 0.796, p > 0.5). The result is suitable to other team sports` results but unusual if we take into consideration the individual sport competitions like tennis or boxing. However the difference is maybe caused that the individuals are cooperating as a team in this situation.